Psychological Perspectives in Interdisciplinary Research on Health Literacy - Markus A. Wirtz; Jürgen Kasper; Anja A. Schulz; Kevin Dadaczynski (European Journal of Health Psychology, 2026)
Abstract: Background: Health literacy enables people to use health information to make self-determined, informed health decisions. Despite the high priority given to this concept in health research and practice, psychological standards and perspectives are not adequately taken into account in existing health literacy models and assessments. Aims: To identify how psychological concepts and theories may improve interdisciplinary comprehensive investigation and psychometric sound assessment of health literacy. Methods: Conceptual and empirical research articles, as well as expertise in network collaborations and in managing research projects on health literacy, are used to identify psychological research challenges. Results: Valid models and assessments of health literacy require integrated consideration of (i) personal literacy aspects (abilities, skills) as well as (ii) information and system features that empower individuals’ health literate behavior. Objective performance indicators meeting psychometric standards for competence modeling provide a valuable supplement to established self-assessments in terms of construct validity and interpretability. Psychological models of information processing and health behavior can contribute to expanding the construct's utility in diagnostic and intervention contexts. Limitations: Conceptual analysis is conducted without a primary data set and requires subsequent empirical testing. C onclusions: Psychological research should specify the information-processing mechanisms underlying health literacy, as well as the interplay between personal (abilities, skills), informational, and systemic (enablers) factors, in accordance with models of health behavior. Performance-based assessments that are oriented toward real-life decision-making and action contexts can help to identify deficits in health literacy more specifically and define concrete intervention strategies aimed at promoting individuals health literate behavior.